Research prospect of human salivary cortisol: a bibliometric analysis - Qin, Shuo; Liu, Juan; Qin, Zhe; Jia, Jing (Frontiers in Psychology, 2025)
BackgroundSalivary cortisol has garnered increasing attention; the aim of this study was to employ bibliometric analysis to identify key papers in this research field and to explore its current status and trends.MethodsData were sourced from Clarivate Analytics’ Web of Science core database, utilizing the search terms ‘TS = (‘Salivary cortisol’) AND (Human) NOT (animal)’. All articles published from January 1, 2004, to September 30, 2024, were included.ResultsA total of 876 articles were identified. The United States has made a significant contribution to this field, with the highest number of publications at 291. The University of California system leads this research area, having published 40 articles. Professor Clemens Kirschbaum has authored 21 articles in this domain. The journal Psychoneuroendocrinology published the largest number of articles, totaling 99, which accounts for 11.3% of the overall articles. Additionally, Psychoneur-oendocrinology was the most cited journal, with 3,681 citations. High-frequency keywords reveal the developmental status and future trends of human salivary cortisol. As a biomarker and signaling molecule, salivary cortisol is closely linked to human gender, personality, psychology, and physiology. We identified that “mental health,” “circadian rhythm,” and “assay” may become focal points of interest in the coming years.ConclusionGlobal publications related to human salivary cortisol were systematically reviewed. CiteSpace and VOSviewer were utilized to analyze their bibliometric characteristics, identify the most cited articles in the field, and determine the leading countries, authors, and institutions, along with the interconnections among them. This analysis aims to elucidate the current status, hotspots, and trends in global research, while providing future development directions for scientific inquiry and medical practitioners.